Repurposing Duloxetine as a Potent Butyrylcholinesterase Inhibitor: Potential Cholinergic Enhancing Benefits for Elderly Individuals with Depression and Cognitive Impairment - Darreh-Shori T.; Baidya A.T.K.; Brouwer M.; Kumar A.; Kumar R. (My University, 2025)
Despite the advent of new treatment strategies, cholinesterase inhibitors (ChEIs) are still the go-to treatment for dementia disorders. ChEIs act by inhibiting the main acetylcholine-degrading enzyme, acetylcholinesterase (AChE). Nonetheless, accumulating evidence indicates that the impact of inhibition of the sister enzyme, butyrylcholinesterase (BChE), could be even broader in older adults due to the multifaceted role of BChE in several biological functional pathways. Therefore, we employed an in silico modeling-based drug repurposing strategy to identify novel potent BChE inhibitors from the FDA drug database. This was followed by in vitro screening and ex vivo enzyme kinetic validation using human plasma samples as the source of BChE. The analysis revealed that the antidepressant drug, duloxetine, inhibited BChE with high selectivity in comparison to AChE. In contrast, two other antidepressants, namely, citalopram and escitalopram exhibited a weak to moderate activity. Ex vivo enzyme inhibition kinetic analyses indicated that duloxetine acted as a competitive inhibitor of BChE with an inhibition constant (Ki) of 210 nM. This Ki value is comparable with 100-400 nM concentration of duloxetine following normal dosages in humans, thereby indicating that duloxetine should be able to induce a pharmacologically and biologically relevant in vivo inhibition of BChE. Additionally, we performed the enzyme inhibition kinetic assessment in parallel for ethopropazine, a known potent selective BChE inhibitor, and physostigmine, a dual inhibitor of AChE and BChE. These analyses indicated that duloxetine should be considered a potent BChE inhibitor since its Ki was comparable with ethopropazine (Ki = 150 nM) but was 4 times smaller than that of physostigmine (Ki = 840 nM). In conclusion, this study reports the discovery of duloxetine being a highly potent selective competitive BChE inhibitor. This, in turn, indicates that duloxetine could be the choice of antidepressive treatment in older adults with both depressive and dementia symptoms since it may offer additional clinically beneficial effects via this secondary mode of cholinergic enhancing action. © 2024 The Authors. Published by American Chemical Society.